Nutrient balance patterns in African livestock systems - Mohamed-Saleem, M.A. (Elsevier, 1998)
Thiss paper presents an overview of the current status, problems and prospects for achieving a better nutrient balance to support varying levels of productivity from the three major livestock systems in Africa. In free range grazing systems, livestock nutrient deficiencies are mainly overcome by moving the animals to better grazing areas. This makes monitoring and managing of nutrients within a system very difficult. Nutrient recovery, cycling and synchronization of manure with other recycled or purchased sources are greater in mixed crop-livestock systems. In these systems, inclusion of nitrogen-fixing leguminous forage/tree crops as companions or rotation crops with cereals further improves the nutrient use efficiency and balance. With more favourable market and policies, commercialized dairy systems are developing around the urban areas of Africa. Such systems heavily depend on purchased feeds and nutrients, and have serious implications for the nutrient balance and sustainability of land use systems in the rural areas which supply the feeds, and for the urban areas because of the risk of pollution from the accumulating animal wastes.